Design and performance of an electrical stimulator for long-term contraction of cultured muscle cells - Mario Marotta; Ramón Bragós; Anna M. Gómez-Foix (BioTechniques, 2004)
Excitability in muscle cells manifests itself as contractility and may be evoked by electrical stimulation. Here we describe an electrical stimulator device applicable to cells seeded on standard multiwell plates and demonstrate how it effectively stimulates synchronous contraction of skeletal muscle C2C12 cells without damaging them. The electrical stimulator of cultured cells (ESCC) consists of two connection cards and a network of platinum electrodes positioned in such way that each well in a row is uniformly stimulated. The ESCC may produce a range of outputs based on the stimulation parameters it receives from a commercial pulse generator and can be placed in a standard cell incubator, allowing for long-term stimulation as required for biochemical and molecular biological assays. We show that a 90-min stimulation of C2C12 myotubes at 50 V, 30 ms of pulse duration, and 3 Hz of frequency enhances glucose metabolism and glycogen mobilization while oppositely modulating the activity ratio of glycogen metabolizing enzymes. Thus, we demonstrate that long-term electrical stimulation of C2C12 myotubes with the ESCC results in contractility and metabolic changes, as seen in exercising muscle.